P(x) = 2x^{3} − x^{2} − 8x + 4

P(x) =

You probably want to break these into smaller questions, or, better, post them as a single paid question - it's too much work really for a quick question I expect.

As an example, the final one:

P(x) = x4 − 3x2 − 4

= (x^2 + a)(x^2 + b)

[ where ab = -4 and a+b = -3, so a = 1, b = -4 ]

= (x^2 + 1)(x^2 - 4)

x^2 = -1 or x^2 = 4

So x = +/- i or +/- 2 are the zeros.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up